Pengaruh Learning EffectBergantung-Waktu dan Deteriorasi Terhadap Penjadwalan Mesin Tunggal - Dian Ayu Nurul Ihsani; Sunarsih Sunarsih (MATEMATIKA FSM, UNDIP, 2014)
Learning effect and deterioration do not fragmentary happen all the time. If both of them simultaneously found, the processing time of the job will increase yet decrease from the plan at once. The actual processing time of jobs are defined by function of their starting times and positions in the sequence. The effect of learning and deterioration on single machine scheduling at this paper is applied at a paper-mill. Learning effect as a result of regular performance-evaluation at this paper-mill reduce the effect of deterioration up to 206,5509 hours. Routing jobs by Earlier Due Date (EDD) rule construct the optimal result under maximum lateness case in this paper than either Most Urgent Job (MUJ) or Shortest Processing Time (SPT) do. The maximum lateness under EDD rule is 13,6% less than sequence that is recently used in that paper-mill.